(untitled) (Precision Medicine Communications, 2022)
In this issue, Ijaz et al, investigated the association of cytochrome CYP2B6 gene polymorphism and urinary adverse effects in Pakistani breast cancer patients taking cyclophosphamide, Ullah and colleagues reviewed the genetic variants affecting efficacy and adverse effects of the standard of care treatment in patients with chronic myelogenous leukemia, Siraj et al, compiled and discussed studies showing genotype-related efficacy and side effects of selective serotonin reuptake inhibitors in patients with the major depressive disorder, Qayyum and colleagues studied the association between cytochrome P450 2C9 gene polymorphisms and blood pressure in response to losartan, and Javed and Akmal reviewed the hepatic adverse effects of anti-mycobacterium tuberculosis drugs and their associations with various genetic variants.